Classpoint as intervention strategy in teaching Business Math - Maryann Yusi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This Action Research aims to determine the effectiveness of utilizing class point in teaching Business Mathematics among grade 11 ABM learners in the Mataas Na Paaralang Neptali A. Gonzales. This study was undertaken to identify the level of performance in Business Mathematics of Grade 11 ABM2 students of Mataas Na Paaralang Neptali A. Gonzales before and after using class point in teaching the subject. The research study participants were 29 ABM2 students during the S.Y. 2021-2022. Data were gathered through the researcher-made Mathematics Performance Test (MPT). A quasi-experimental design was used in this study. Learner-respondents came from 11 ABM2 at Mataas Na Paaralang Neptali A. Gonzales. Data were generated from the Pre-test to determine the learners' prior knowledge before using the Classpoint. Weekly Assessment in a form of teacher-made learning activity sheets which undergone quality assurance process to determine students' performance while using the classpoint in teaching Business Mathematics and Posttest was administered to determine the learners' mastery of Business Mathematics after using the classpoint. After using classpoint in teaching Business Math, there is a significant difference between the pre-test and the post test mean scores. This suggests that using class points effectively has a beneficial effect on students' achievement test.